On generalized statistical convergence of order ? of sequences of fuzzy numbers - Karakas, Abdulkadir; Altin, Yavuz; Altinok, Hifsi (Ios Press, 2014)
In this article we introduce the concepts of Delta(m)(lambda)-statistical convergence of order beta and strong Delta(m)(lambda p)-summability of order beta for sequences of fuzzy numbers. Also, we establish some relations between the Delta(m)(lambda)-statistical convergence of order beta and strong Delta(m)(lambda p)-summability of order beta and we define w(lambda)(beta) (Delta(m), F, f, p), where f is a modulus function and give some inclusion relations.
Keywords: Fuzzy number; statistical convergence; Cesaro summability; modulus function